Effect of caveolin-1 knockdown on the protein composition of extracellular vesicles secreted by non-small cell lung cancer cells - G. O. Skryabin; A. V. Komelkov; P. B. Kopnin; I. I. Nikishin; S. A. Kuzmichev; E. M. Tchevkina (Успехи молекулярной онкологии, 2021)
Background. Recent data show evidence that lipid rafts (LR) proteins could be involved in the formation of exosomes and the sorting of proteins that make up the exosomal cargo. Such data are available for flotillins, structural and functional components of flatted rafts. The presence of the main component of caveolar rafts, caveolin-1 (Cav-1), has been shown in exosomes produced by some cancer cells; however, its possible participation in the regulation of the protein composition of exosomes has not been studied previously.Materials and methods. Knockdown of Cav-1 by transduction of a lentiviral vector expressing precursors of short hairpin ribonucleic acid to Cav-1; isolation (by ultracentrifugation) and analysis (transmission electron microscopy, nanoparticle tracking analysis) of extracellular vesicles (EVs) from non-small cell lung cancer cells (NSCLC) H1299; analysis of proteins in cells and in EVs by immunoblotting.Results. Analysis of the effect of Cav-1 expression on the composition of EV proteins associated with exosome biogenesis revealed a decrease in the level of Alix and TSG101, an increase in the level of LR proteins and the absence of changes in the level of tetraspanin CD9. Conclusion. The obtained data demonstrate a Cav-1-dependent changes in the composition of EVs, indicating a change in the ratio of vesicles formed by the various molecular mechanisms.